Microscopic Transsphenoidal Resection of Giant Pituitary Adenomas: Analysis of the Factors Limiting the Degree of Resection in 73 Cases - Pei, Zhijie; Wang, Jiaxing; Mu, Shuwen; Feng, Tianshun; Wang, Meina; Yu, Shentong; Wei, Liangfeng; Fang, Yi; Wang, Shousen (Frontiers in Neurology, 2022)
Abstract Purpose: To analyze the risk factors affecting the gross-total resection of giant pituitary adenomas using a transsphenoidal approach under a microscope to provide a reference basis for formulating an appropriate surgical strategy. Methods: The clinical data of patients who underwent microscopic transsphenoidal resection of giant pituitary adenomas in a single center from January 2011 to December 2020 were retrospectively analyzed. Based on magnetic resonance imaging and surgical records, the predictive factors affecting the gross-total resection of giant pituitary adenomas under microscopy were determined through univariate and multivariate analyses. Results: A total of 73 patients with giant pituitary adenomas underwent transsphenoidal microsurgery. Gross-total resection was performed in 19 cases (26%), subtotal resection in 31 cases (42%), partial resection in 21 cases (29%), and the degree of resection was less than 50% in only two cases (3%). After binary logistic analysis, it was found that it was more difficult to completely remove giant pituitary adenomas with a Knosp grade 3–4 (odds ratio [OR] = 0.214, 95% confidence interval [CI]: 0.05–0.917; P = 0.038), greater proportion of tumor suprasellar volume (odds ratio = 0.937, 95% confidence interval: 0.898–0.978; P = 0.003), and intraoperative evidence of invasion of the cavernous sinus (odds ratio = 0.187, 95% CI: 0.039–0.898; P = 0.036). Conclusion: It is difficult to remove a giant pituitary adenoma invading the cavernous sinus completely with a higher degree of invasion of the suprasellar region using microscopic transsphenoidal surgery. The combined application of multiple surgical methods can help to improve the degree of resection during a single operation.